On liberation: Education and ideology in Paulo Freire's thought - Trezzi, Clóvis (2022)
Liberating Education is the starting point for overcoming sectarianism, which arises from an uncritical reading of the world based on extremist ideologies. The article discusses the relationship between Liberating Education and ideologies, asking about the role of education in this process of humanization of the human being. The paper aims to establish a relationship between Liberating Education and overcoming ideological sectarianism, emphasizing that this overcoming only occurs through dialogue. The path taken is a hermeneutic reading of some books by Paulo Freire that revolve around the Pedagogy of the Oppressed. In the conceptualization of ideology, Freire is put in contact with the thought of Paul Ricoeur. The paper concludes that the role of the school is not to break sectarianism, but to help human beings to do so.